UPAYA PENANGGULANGAN SAMPAH ORGANIK DI DESA MAOS LOR CILACAP MENGGUNAKAN KOMPOSTER AYUN - Nurlinda Ayu Triwuri; Rosita Dwityaningsih; Oto Prasadi; Eka Dyah Puspita Sari (LPPM Universitas Putera Batam, 2019)
Population growth and settlements have significant consequences on basic problems. One of the main problems that arises and needs to be planned is waste problem. Large amount of unhandling landfill causes various problems, both directly and indirectly for the city population, especially the community members in Desa Maos Lor, Dusun Tengah RW 11 who own a Waste Bank. The problem from Waste Bank is the organic waste that is not utilized and managed optimally, instead it is allowed to accumulate and rot, so it pollutes the environment. The potential method for handling organic waste is by applying anaerobic composter technology to produce fertilizer or compost, which is a swing composter. The composition in the swing composter consists of husk as the base, compost as the starter, fine organic waste (in the form of residual waste or kitchen waste), then it is covered with husk. To speed up the occurrence of decay, the kitchen waste is chopped into small size. Then, the composter is swung 5 to 10 times for mixing it with microorganisms. Next step is letting the swing composter for 4 months. Liquid organic fertilizer and solid organic fertilizer can be used by residents of Desa Maos Lor Dusun Tengah RW 11 to grow crops.